Perbandingan Efektivitas Simulasi PhET dan Alat Peraga Mobil-Mobilan Terhadap Peningkatan Pemahaman Konsep GLB dan GLBB (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2025)
This study aims to compare the effectiveness of the PhET simulation of pacing and toy cars accompanied by discussions on improving the understanding of the concepts of Uniform Linear Motion (GLB) and Uniformly Accelerated Linear Motion (GLBB). The background of this study is based on students' difficulties in visualizing motion quantities, so that learning media that can present concrete and digital representations are needed. The research method used a quasi-experimental design with a Pretest–Posttest Two Group Design in two grades of high school. The instrument was 30 validated multiple-choice questions. Analysis of understanding improvement was carried out using normalized gain (N-Gain). The results showed that class E7 with the PhET simulation achieved 69.44% in the high improvement category, while class E3 with the toy cars achieved 75% in the same category. These findings indicate that both media are effective, but the toy cars provide a more even improvement because concrete experiences make it easier for students to connect theory with real phenomena. This study emphasizes the importance of selecting learning media that suit the characteristics of the concept and students' needs to optimize physics learning outcomes.